2011
DOI: 10.1186/1472-6963-11-242
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to effective discharge planning: a qualitative study investigating the perspectives of frontline healthcare professionals

Abstract: BackgroundStudies have shown that effective discharge planning is one of the key factors related to the quality of inpatient care and unnecessary hospital readmission. The perception and understanding of hospital discharge by health professionals is important in developing effective discharge planning. The aims of this present study were to explore the perceived quality of current hospital discharge from the perspective of health service providers and to identify barriers to effective discharge planning in Hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 36 publications
2
114
0
7
Order By: Relevance
“…Pethybridge (2004) reported on unidisciplinary, multidisciplinary and transdisciplinary types of leadership and teamworking, each type suggested variations in how healthcare professionals interacted and worked together. A repeated theme in these studies on discharge in acute care is a lack of clarity about health care professionals' roles and responsibilities and problems with communication between professionals, with a shared concern that no one takes overall responsibility for discharge (Connolly et al, 2009;Greysen et al, 2012b;Pethybridge, 2004;Wong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pethybridge (2004) reported on unidisciplinary, multidisciplinary and transdisciplinary types of leadership and teamworking, each type suggested variations in how healthcare professionals interacted and worked together. A repeated theme in these studies on discharge in acute care is a lack of clarity about health care professionals' roles and responsibilities and problems with communication between professionals, with a shared concern that no one takes overall responsibility for discharge (Connolly et al, 2009;Greysen et al, 2012b;Pethybridge, 2004;Wong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Problems with communication and discharge have been attributed to professional hierarchy and insufficient contact among professionals (Greysen et al, 2012b;Wong et al, 2011). Factors identified as important to effective interprofessional collaboration and teamwork in discharge include sharing of information, trust, respect, communication, a learning culture and facilitative leadership (Pethybridge, 2004;Reeves, Lewin, Espin & Zwarenstein 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Uma das exigências educacionais atuais em saúde, de acordo com a OMS (21) , é a busca e aplicação de estratégias que beneficiem as atitudes de saúde e o envolvimento consciente dos cidadãos na superação de dúvidas e temores relacionados aos cuidados a serem implementados no processo saúde-doença, sem restrições geográficas ou socioculturais. Há a necessidade de estabelecer um protocolo de orientações para alta, de modo a facilitar e melhorar sua efetividade (22) . O processo de alta envolve um trabalho em conjunto, desde as orientações antes da alta e a realização de encaminhamentos para continuidade à assistência pela equipe multiprofissional, o que pode influenciar assim, no índice de reinternações (23) .…”
Section: Discussionunclassified
“…Difficulties in discharge planning have been an area of concern for more than 20 years and the challenge of improving the planning session and addressing communication between professions is described in a comparative study based on data from Sweden and the UK [3] . However, it would seem that problems related to communication among participants in the traditional discharge planning process are examined in many ways [18][19][20] . Person-centred nursing, where the nursing staff establish relationships with the patient, and a more modern way of communicating are perhaps needed if progress is to be made in this area [21] .…”
mentioning
confidence: 99%
“…Wong et al found in a qualitative study from Hong Kong that barriers to effective discharge planning were lack of standardised, hospital-wide discharge planning and a policy-driven approach. A further potential barrier was lack of communication and co-ordination among different stakeholders and patients [20] . Difficulties in discharge planning have been an area of concern for more than 20 years and the challenge of improving the planning session and addressing communication between professions is described in a comparative study based on data from Sweden and the UK [3] .…”
mentioning
confidence: 99%